2018
DOI: 10.1186/s12962-018-0162-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of secukinumab versus other biologics and apremilast in the treatment of active Psoriatic arthritis: a Finnish perspective

Abstract: ObjectiveTo study cost-effectiveness of an interleukin (IL)-17A inhibitor secukinumab, with other biologics and apremilast in patients with Psoriatic arthritis (PsA) from payer perspective in Finland.MethodsIn this semi-Markov model, subcutaneous (SC) secukinumab was compared with SC treatments etanercept and its biosimilar, certolizumab pegol, adalimumab and its biosimilar, golimumab, ustekinumab, intravenous (IV) treatment infliximab, as well as oral non-biologic apremilast. Patients without prior exposure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Conversely, an Argentinian cost-effectiveness analysis over a lifetime horizon of secukinumab versus other biologics for the treatment of PsA found that among biologic-naïve PsA patients without psoriasis, secukinumab dominated adalimumab, while among those biologic-naïve with psoriasis and those biologic-experienced, secukinumab was cost effective versus adalimumab [ 23 ]. Similarly, a Finnish cost-effectiveness analysis over a lifetime horizon of secukinumab versus other biologics in PsA found that secukinumab dominated adalimumab in biologic-naïve patients without moderate to severe psoriasis, while it was cost effective against adalimumab in biologic-naïve patients with moderate to severe psoriasis and biologic experienced patients [ 24 ]. Secukinumab also dominated adalimumab for the treatment of PsA in a Canadian cost-effectiveness analysis over a lifetime perspective that included both biologic-naïve and biologic-experienced patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, an Argentinian cost-effectiveness analysis over a lifetime horizon of secukinumab versus other biologics for the treatment of PsA found that among biologic-naïve PsA patients without psoriasis, secukinumab dominated adalimumab, while among those biologic-naïve with psoriasis and those biologic-experienced, secukinumab was cost effective versus adalimumab [ 23 ]. Similarly, a Finnish cost-effectiveness analysis over a lifetime horizon of secukinumab versus other biologics in PsA found that secukinumab dominated adalimumab in biologic-naïve patients without moderate to severe psoriasis, while it was cost effective against adalimumab in biologic-naïve patients with moderate to severe psoriasis and biologic experienced patients [ 24 ]. Secukinumab also dominated adalimumab for the treatment of PsA in a Canadian cost-effectiveness analysis over a lifetime perspective that included both biologic-naïve and biologic-experienced patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secukinumab greatly improved nail psoriasis, as assessed by NAPSI (Reich et al, 2018). Secukinumab was a cost-effective biological in the treatment of PsA with the highest net monetary benefit than other biologicals in Finland (Purmonen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%